333 EFFECT OF KEPIVANCE ON THE INCIDENCE OF MUCOSITIS, HOSPITAL STAY, AND TOTAL PARENTERAL NUTRITION IN PATIENTS UNDERGOING STEM CELL TRANSPLANTATION. Issue 1 (1st January 2007) - D'Cunha, N.; Idowu, M.; Williams, B.; Cobos, E.; Chriva-Internati, M.; Hardwicke, F.
Abstract : Kepivance is a keratinocyte growth factor (KGF) that stimulates the growth of cells in the skin, mouth, stomach, and colon. It has been suggested that Kepivance may reduce the incidence and severity of oral mucositis in patients receiving a total body irradiation (TBI) conditioning regimen followed by autologous stem cell rescue. Very few studies have shown the effect of Kepivance on chemotherapy-induced mucositis in patients receiving allogeneic/autologous stem cell transplantation. We analyzed retrospectively the charts of all patients who underwent stem cell transplantation in 2005-2006 at Texas Tech University Health Science Center. The charts of 36 patients were reviewed, of which 21 received Kepivance. The decision to receive Kepivance was judged by the treating physician. Patients with a high risk of developing mucositis from intensive chemotherapy, older patients, type of conditioning regimen, and type of transplant dictated which patient should receive Kepivance. Conditioning regimens in the Kepivance group were as follows: high-dose melphalan (10); TBI, VP-16, and cyclophosphamide (1); BCNU, VP-16, and cyclophosphamide (2); fludarabine and melphalan (1); melphalan and VP-16 (1); busulfan and fludarabine (6). Conditioning regimens in the non-Kepivance group were as follows: melphalan and busulfan (1); melphalan and fuldarabine (2); BCNU, VP-16, and cyclophosphamide (4); high-dose melphalan (8). Of 21 patients who received Kepivance, 12 patients received autologous transplant and 9 patients received allogeneic transplants. Of the 21 patients who received Kepivance, 8 experienced grade II-III mucositis compared with 3 of 15 patients in the non-Kepivance group. No patients in both groups experienced grade IV mucositis. In both groups, 50% of the patients required total parenteral nutrition (TPN). The average length of stay in patients who received kepivance was 31 days versus 36 days in patients who did not receive Kepivance. Day 100 mortality in the Kepivance group was five, all of whom received allogeneic transplant, whereas there was only one death (who received allogeneic transplantation) in the non-Kepivance group. We concluded that Kepivance reduces the hospital stay in patients undergoing stem cell transplantation; however, there were no noted benefits of Kepivance in TPN requirement or the incidence of mucositis. This may be due to physician bias in selecting patients who should receive Kepivance. High-risk patients received Kepivance. A randomized clinical trial is needed to confirm these results.